Discrimination between two lung diseases using chest radiographs - Mohd. Noor, Norliza (2005)
Economic considerations make the conventional chest radiograph (X-ray) film an important ingredient in the diagnostic process. An initial clinical investigation for patients with suspected lung ailments is the study of the chest X-rays. The problem of detection for diseases in their early stages are well known using X-ray. A technique involving wavelets coefficient as the feature vector and Andrew's Curve has been proposed for detection of Mycobacterium Tuberculosis (MTB). This paper presents new and important results whereby lung cancer (LC) may be detected and differentiated from MTB. A method to calculate misclassification probabilities is given.